Molecular level control of the capacitance of two-dimensional covalent organic frameworks: role of hydrogen bonding in energy storage materials - Chandra, S.; Chowdhury, D.R; Addicoat, M.; Heine, T.; Paul, A.; Banerjee, R. (Chemistry of Materials, 2017)
Two-dimensional redox-active covalent organic frameworks (COFs) are ideal materials for energy storage applications due to their high surface area, extended pi conjugated structure, tunable pore size, and adjustable functionalities. Herein, we report the synthesis and super capacitor application of two redox active COFs [TpPa-(OH)(2) and TpBD-(OH)(2)] along with the role of their redox active functional groups for the enrichment of specific capacitance. Of these COFs, TpPa-(OH)2 exhibited the highest specific capacitance of 416 F g(-1) at 0.5 A g(-1) current density in three electrode configuration while the highest specific capacitance was 214 F g(-1) at 0.2 A g(-1) current density in two electrode configuration. Superior specific capacitance was due to emergence of excellent pseudocapacitance by virtue of precise molecular level control over redox functionalities present in the COF backbone. This COF also demonstrated 66% capacitance retention after 10 000 cycles along with 43% accessibility of the redox-active hydroquinone (H2Q) moieties in three electrode configuration while the capacitance retention was 88% after 10 000 cycles in two electrode configuration. Exceptionally high specific capacitance of TpPa-(OH)(2) was due to the reversible proton-coupled electron transfer (2H(+)/2(e-)) of hydroquinone/benzoquinone (H(2)Q/Q) moieties wherein H(2)Q and Qhad comparable chemical stabilities during redox cycling that originated from H-bonding, which was supported by calculated structures.